2022
DOI: 10.1242/dev.200295
|View full text |Cite
|
Sign up to set email alerts
|

‘Neighbourhood watch’ model: embryonic epiblast cells assess positional information in relation to their neighbours

Abstract: In many developing and regenerating systems, tissue pattern is established through gradients of informative morphogens, but we know little about how cells interpret these. Using experimental manipulation of early chick embryos including misexpression of an inducer (VG1 or ACTIVIN) and an inhibitor (BMP4), we test two alternative models for their ability to explain how the site of primitive streak formation is positioned relative to the rest of the embryo. In one model, cells read morphogen concentrations cell-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…These relativistic properties might provide robustness against variation in absolute expression because of genetic and environmental perturbations. Indeed, in several developmental contexts it has been suggested that relative fold-changes, rather than absolute concentration changes, drive robust responses to noisy morphogen or signaling gradients, such that cells can correctly ascertain their spatial positions relative to their neighbors ( Simsek and Özbudak, 2018 ; Lee et al., 2022 ). There is precedent for Wnt ligands inducing a fold-change in signal transduction to the nucleus rather than a change in absolute level ( Goentoro and Kirschner, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…These relativistic properties might provide robustness against variation in absolute expression because of genetic and environmental perturbations. Indeed, in several developmental contexts it has been suggested that relative fold-changes, rather than absolute concentration changes, drive robust responses to noisy morphogen or signaling gradients, such that cells can correctly ascertain their spatial positions relative to their neighbors ( Simsek and Özbudak, 2018 ; Lee et al., 2022 ). There is precedent for Wnt ligands inducing a fold-change in signal transduction to the nucleus rather than a change in absolute level ( Goentoro and Kirschner, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…Like WNT8C , BMP4 is strongly expressed in the area opaca and the marginal zone but with an opposite gradient (strongest anteriorly), and disappears from the area opaca at primitive-streak stages ( Streit et al, 1998 ). Although BMP signalling acts as an inhibitor of primitive streak formation and cVG1 expression, a recent study in the chick embryo suggested that the primitive streak is positioned by the balance between cVG1/NODAL and BMP signals, assessed locally by cells ( Lee et al, 2022 ). Moreover, in mouse embryos, BMP signalling from extra-embryonic tissue induces WNT3 in the epiblast to amplify NODAL signalling and thus position the primitive streak ( Ben-Haim et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…These relativistic properties might provide robustness against variation in absolute expression due to genetic and environmental perturbations. Indeed, in several developmental contexts it has been suggested that relative fold-changes, rather than absolute concentration changes, drive robust responses to noisy morphogen or signaling gradients, such that cells can correctly ascertain their spatial positions relative to their neighbors (Simsek and Özbudak, 2018; Lee et al, 2022). There is precedent for Wnt ligands inducing a fold-change in signal transduction to the nucleus rather than a change in absolute level (Goentoro and Kirschner, 2009).…”
Section: Discussionmentioning
confidence: 99%